Hubungan Pengetahuan dan Sikap Orang Tua terhadap Pencegahan Kekerasan Seksual pada Anak di Kota Administrasi Jakarta Selatan Tahun 2023 - Annisa Anindita Rahmania (2024)
Violence with child victims continues to increase by 14% from 2021 to 2023 and sexual violence is the highest type that occurs against child victims in the city of South Jakarta. This research aims to determine the relationship between the knowledge and attitudes of parents toward preventing sexual violence against children. The research was conducted using a cross-sectional method with the population being 760.769 heads of families aged 19-64 years, a random sampling method was used and a total sample of 296 respondents who were parents, both fathers and mothers. Data collection used a questionnaire adapted from previous research questionnaires and had been tested for validity and reliability. Data analysis used univariate analysis, and bivariate analysis using the chi-square test. The results of the analysis show that there is a significant relationship between parental knowledge (p-value = 0.05) and parental attitudes (p-value = 0.022) towards preventing sexual violence in children. This can happen because it is influenced by the educational level of the respondents, the majority of whom are in high school, because the more information an individual receives, the higher their knowledge and the more positive attitudes they will form in preventing sexual violence against children. It is recommended that parents increase their knowledge by utilizing social media and the internet to obtain additional information regarding efforts to prevent sexual violence against children.